DATA VISUALISASI SEBAGAI PENDUKUNG INVESTIGASI MEDIA SOSIAL - Suwito Pomalingo; Bambang Sugiantoro; Yudi Prayudi (ILKOM Jurnal Ilmiah, 2019)
Social media is an application that can make everyone interact with each other and can consume information by sharing content quickly, efficiently and real time. Various kinds of information about someone's activities that we can find on social media, making social media can help to conduct investigations. Some research, using visualization with several graph methods to facilitate the process of analyzing data on social media that is so abundant. But the data used only comes from one social media, while there is still a lot of information on other social media that can be used as data sources for analysis purposes. In this study visualization using the directed graph method will be carried out, then calculate the value of network property and the value of centrality to find out which nodes have many activities which will be carried out in depth searches to find patterns of interaction or activity. Based on the results of the calculated centrality, it is found that on Twitter and Instagram accounts there are many interactions, this can be seen in the value of the indegree and outdegree node. Based on the results of the analysis in this study, information that is important for investigating social media is obtained, such as information about user profiles, posts, comments, preferred social media pages, location, and timestamp, all of which are connected by a line that shows the relationship between the node.